2021
DOI: 10.1007/s10072-020-05035-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lockdown during SARS-CoV-2 outbreak on behavioral and psychological symptoms of dementia

Abstract: Background During Covid-19 pandemic, the Italian government adopted restrictive limitations and declared a national lockdown on March 9, which lasted until May 4 and produced dramatic consequences on people’s lives. The aim of our study was to assess the impact of prolonged lockdown on behavioral and psychological symptoms of dementia (BPSD). Methods Between April 30 and June 8, 2020, we interviewed with a telephone-based questionnaire the caregivers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 24 publications
(32 reference statements)
2
50
3
Order By: Relevance
“…It is striking that no other study has so far reported sleep disorder as a worsening of a pre-existing neuropsychiatric symptom. 25,30 In contrast, agitation-aggression has been reported as a frequent symptom, similar to aberrant motor behavior in patients with AD and frequent neuropsychiatric symptoms when evaluating all dementias in general 25,30,33 (Table 4); however, a minor increase was observed in our study, but it was not significant. The new-onset neuropsychiatric symptoms during pandemic lockdown were reported as a higher frequency in AD (26.7%) than other dementias; in this same study from Cagnin A. et al, the most common symptoms reported were sleep disorders, irritability, and agitation-aggression.…”
Section: Discussioncontrasting
confidence: 56%
“…It is striking that no other study has so far reported sleep disorder as a worsening of a pre-existing neuropsychiatric symptom. 25,30 In contrast, agitation-aggression has been reported as a frequent symptom, similar to aberrant motor behavior in patients with AD and frequent neuropsychiatric symptoms when evaluating all dementias in general 25,30,33 (Table 4); however, a minor increase was observed in our study, but it was not significant. The new-onset neuropsychiatric symptoms during pandemic lockdown were reported as a higher frequency in AD (26.7%) than other dementias; in this same study from Cagnin A. et al, the most common symptoms reported were sleep disorders, irritability, and agitation-aggression.…”
Section: Discussioncontrasting
confidence: 56%
“…Several surveys have documented increases in symptoms during similar COVID-19 restrictions among a signi cant proportion of people with dementia such as psychological distress (Giebel et al 2021, Manini et al 2021, cognitive worsening (Canavelli et al 2020) with impacts on communication and mood (Tsapanou et al 2021) and falls (Barguilla et al 2020). Stress has been observed among a signi cant proportion of carers (Altieri andSantangelo 2021, Caneyville et al 2020;Cagnino et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Where asked, people with dementia themselves were concerned about declining skills and abilities [10][11][12][13][14]. Increases in neuropsychiatric symptoms, behaviour problems, depression, anxiety, and loneliness were also reported by carers [11,[15][16][17][18][19][20][21][22][23], although some studies found only limited impacts in these areas [24,25]. For example, Thyrian, et al [24] observed rates of depression, anxiety, and loneliness that were comparable to or even lower than age-equivalent norms for the general population of older people recorded before the pandemic.…”
Section: Introductionmentioning
confidence: 99%